Descriptions of depression and depression treatment in older Hispanic immigrants in a geriatric collaborative care program. (3rd August 2018) - Camacho, David; Estrada, Elena; Lagomasino, Isabel T.; Aranda, Maria P.; Green, Jennifer
ABSTRACT: Objectives: To explore experiences with depression and depression treatment among older Hispanic immigrants participating in a collaborative care program of psychotherapy and antidepressant medication. Method: Semi-structured, in-depth interviews were conducted with 14 older Spanish-speaking Hispanic immigrants with major depression who participated in a collaborative care program within a public sector specialty geriatric clinic in Los Angeles, CA. Results: Findings revealed that participants used various idioms to describe their experiences with depression, and that depression had a strong impact on functioning. Other findings indicated that depression was caused by various psychosocial problems, antidepressants were helpful in reducing depression, and that bilingual psychotherapists provided a welcoming and safe environment to express emotions and find solutions to problems. Conclusion: Results revealed participants' experiences with depression and the impact of participating in a collaborative care intervention for depression. Findings from this project should be used to inform future geriatric interventions for older Hispanic immigrants in the USA.